The Conflict OF Culture AND Self-Identity AND THE Indian Diaspora IN Jhumpa Lahiri's The Namesake (Journal of Namibian Studies : History Politics Culture, 2022)
Today's era has become the era of technology and due to the development of this technology, the distances between cities and country boundaries have also been reduced, due to which today we do not hesitate at all to leave our country for a better life and go to another country in search of work and to be successful. Due to this rapidly developing technology, cooperation in cultural relations has increased. Although it is often seen that leaving one's own country is a very difficult time. But in today's time, the distance that comes in mutual relationships is to a great extent overcome by getting closeness through Facebook, WhatsApp, Instagram and other similar means. But still issues like leaving one's home and going to another country and creating a new identity, living within the limits of the ideals of one's descendants, adopting the lifestyle of that country, etc. still remain. In this research paper, an attempt has been made to understand the struggles of the second generation of Indian immigrants with special reference to Jhumpa Lahiri's novel The Namesake. Jhumpa Lahiri has portrayed well through the characters in 'The Namesake' the term diaspora and its role, the lives of first and second generation immigrants and their struggle for identity and belonging.  Jhumpa Lahiri herself is also the child of Indian immigrants whose parents were middle class Bengalis. She was born in London and grew up in America's Rhode Island. Therefore, The Namesake is in a way the autobiography of Jhumpa Lahiri because in this novel Lahiri has prominently portrayed the experiences of the second generation of Indian immigrants.